Experience in implementing joint Belarusian-Chinese master’s programmes - Medvedev, Dmitry G.; Marmysh, Dzianis E. (University Pedagogical Journal, 2026)
This article presents the experience of implementing joint educational programmes between Dalian University of Technology and the Belarusian State University within the framework of the Joint Institute of Dalian University of Technology and Belarusian State University for the preparation of students at the master’s level. It analyses the motives of Chinese students who decide to continue their education in a master’s programme, as well as ways that can lead to the intensification and increase in the number of joint educational programmes with leading Chinese universities. It is noted that strategic cooperation between Belarus and China is not limited to educational programmes alone; it contributes to the deepening integration of academic and scientific environments, which can potentially lead to the opening of joint educational institutions and research centres.